Tatalaksana Serangan Gout Akut: Sebuah Tinjauan dari Tiga Pedoman - Irwin Priyatna Kusumah; Florence Pribadi; Bella Meylani Lifindra; Helen Octavia Djoenaydy; Kevin Luke (Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
Acute gout flare is one spectrum of gout disease. The flare is characterized by severe acute pain with signs of inflammation at the joint. Currently, there are three primary guidelines in managing gout flares, namely American College of Rheumatology (ACR), European League Against Rheumatism (EULAR), and Indonesian Rheumatology Association (IRA). The objective of this review is to analyze the management of gout flares among these guidelines. We compared three guildelines on managing acute gout flare based on their acute therapy initiation time, first-line treatment, additional treatment, and urate-lowering therapy initiation. Additional literature search was also conducted on PubMed and ScienceDirect to provide additional information to the guideline. All guidelines agreed that management of gout flares should be initiated as early as possible with colchicine or NSAIDs based on patient condition and contraindications. Oral or injected corticosteroid should be considered in patient with renal impairment or contraindications to colchicine or NSAIDs. In conclusion, most recommendations from three guidelines were similar. IRA 2018 are still suitable for managing acute gout flare for Indonesian population